The awareness and implementation of the response to intervention strategy among kindergarten teachers in managing behavioral problems in preschool - Almutlaq, Hajar; Alhossyan, Fawaz (Edelweiss Applied Science and Technology, 2025)
The Response to Intervention (RTI) strategy is a systematic and evolving approach designed to support children encountering behavioral and academic challenges. This study aimed to assess the level of awareness and implementation of the RTI strategy among kindergarten teachers in the central region of the Kingdom of Saudi Arabia. A descriptive methodology was utilized to answer the study's questions, with a sample consisting of 72 kindergarten teachers. Data were analyzed to describe levels of awareness, implementation, and challenges using appropriate statistical methods, including means and standard deviations. Pearson correlation coefficient was used to examine the relationship between variables, and Cronbach’s alpha was calculated to confirm the reliability of the instrument. The results revealed that the level of awareness among teachers regarding the RTI strategy was high, while the level of implementation was moderate. Moreover, the findings indicated significant challenges that obstruct the effective application of the strategy in classroom settings. The study concluded with recommendations, such as the need to enhance training programs aimed at preparing kindergarten teachers with practical knowledge on RTI implementation, and highlighted the importance of providing continuous technical and administrative support to facilitate more effective practice.